PERAN SISTEM AKUNTANSI MANAJEMEN DALAM ORGANIZATIONAL LEARNING : Upaya Menghadapi Dinamika Organisasi - Faisal, Faisal; Rahayu, Dyah Sih (JURNAL BISNIS STRATEGI, 2001)
The increasingly competitive markets and technological advancement have demend the practicioners and accedemicians to focused on interrelationship between corporate strategy and management accounting system (MAS). In management accounting the interdependent complexity of strategy, structure and systems are integrated through the concept of "organizational learning".Since management accounting system captures and disseminates information about firm performance, organizational learning concept that the emphasis to "knowledge" is a critical asset directly impacts management function hence, organizational learning provides a logical thinking how corporate strategy relates to organizational system and process, namely MAS.This paper discussed how the role MAS in organizational learning to faced organizational dynamics.